The management of retrorectal tumours: tertiary centre retrospective study. Issue 2 (20th April 2022) - Burke, Joshua R.; Shetty, Kunal; Thomas, Owen; Kowal, Mikolaj; Quyn, Aaron; Sagar, Peter
Abstract: Aim: Tumours of the retrorectal space are uncommon, pathologically heterogeneous, and difficult to diagnose, with ongoing controversy over their surgical management. The aim of this study was to evaluate the surgical management of a consecutive series of patients who had undergone excision of primary retrorectal tumours (PRRTs) at a tertiary referral centre. Method: Patients were identified from a prospectively maintained database between 1 March 2001 and 1 August 2021. Electronic patient records were reviewed for demographics, preoperative imaging, operative details, histology, and follow-up. A chi-squared test was used to assess the statistical significance of findings. Results: A total of 144 patients were included in the study. Of these, 103 patients were female (71.5 per cent), 46 patients (31.9 per cent) presented incidentally, and 99 of the patients had tumours located below S3 (68.7 per cent). Overall, 76 patients underwent a transperineal approach (52.7 per cent) with the most common findings of a benign tailgut cyst occurring in 59 (40.9 per cent) of cases. Preoperative MRI predicted urovascular and pelvic sidewall involvement assessed intraoperatively with a sensitivity of 83.3 and 90 per cent and a specificity of 98.1 and 98 per cent respectively. Risk of malignancy in solid tumours was 31.4 versus 8.8 per cent in cystic tumours (relative risk 3.5, 95 per cent c.i. 1.6 to 7.6, P < 0.001). Major complications (Clavien–Dindo grade III and above) occurred in eight patients (5.6 per cent) and all-cause long-term mortality was 4.8 per cent (seven patients). Discussion: PRRTs can be safely excised with minimal complications in specialized centres by surgical teams with the relevant expertise. This study questions the conservative management of cystic tumours and given the risk of solid tumour malignancy, supports surgical management. Abstract : There remains ongoing controversy over the surgical management of retrorectal tumours. The manuscript demonstrates that these tumours can be safely excised with minimal complications and brings into question the conservative management of cystic tumours given the risk of solid tumour malignancy.